Voting for a social Europe? European solidarity and voting behaviour in the 2019 European elections. (March 2022) - Pellegata, Alessandro; Visconti, Francesco
This article investigates whether public preferences for European solidarity are associated with vote choices in the 2019 European elections. After multiple crises, the politicisation of European Union affairs has increased, polarising voters and parties between those favouring the redistribution of risks across member states and those prioritising national responsibility in coping with the consequences of the crises. We expect pro-solidarity voters to be more prone to vote for green and radical-left parties and less prone to vote for conservative and radical-right parties. Testing these hypotheses in 10 European Union countries with original survey data, we find that green and radical-left parties profited from European solidarity voting only in some countries, while being pro-solidarity reduced the likelihood of voting for both moderate and radical-right parties in each sample country.